2014
DOI: 10.3748/wjg.v20.i8.2051
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of inflammation and microbiota dynamics in a model of mild chronic dextran sulfate sodium-induced colitis in mice

Abstract: Dysbiosis contributes to the local and systemic inflammation that occurs in the DSS model of colitis; however, chronic bowel inflammation is maintained even after recovery from dysbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 34 publications
9
70
1
2
Order By: Relevance
“…We demonstrated that Clostridium cluster XIVa species were significantly underrepresented upon DSS challenge, confirming previous observations in both human and experimental IBD (2,(48)(49)(50). However, oral administration of UDCA or its taurine or glycine conjugates was able to provoke an enrichment of these species compared with placebo-treated mice.…”
Section: Discussionsupporting
confidence: 77%
“…We demonstrated that Clostridium cluster XIVa species were significantly underrepresented upon DSS challenge, confirming previous observations in both human and experimental IBD (2,(48)(49)(50). However, oral administration of UDCA or its taurine or glycine conjugates was able to provoke an enrichment of these species compared with placebo-treated mice.…”
Section: Discussionsupporting
confidence: 77%
“…This may indicate a mild severity of inflammation in the present DSS model. On the other hand, IL-17 is a delayed-type immune reaction cytokine produced by Th17 and by CD8+ T cells during chronic inflammation [29, 30]. DSS colitis represents an acute model of colitis [30]; this idea supports that we could not detect significant changes of IL-17 expression on the present DSS colitis.…”
Section: Discussionsupporting
confidence: 71%
“…Microbial dysbiosis in IBD is usually characterized by global reductions in bacterial diversity and changes in the abundances of certain species, including higher proportions of aerotolerant bacteria such as Enterococcaceae and Enterobacteriaceae species (66)(67)(68). Notably, a similar change in the intestinal microbiota was found in mice fed normal (low-fat, polysaccharide-enriched) chow (69)(70)(71).…”
Section: Reductions In L Casei Recasupporting
confidence: 49%